Preference‐based patient participation in intermediate care: Translation, validation and piloting of the 4Ps in Norway - Linda A. H. Kvæl; Astrid Bergland; Ann C. Eldh (Health Expectations)
Abstract Introduction The implementation and evaluation of patient participation to obtain high‐quality transitional care for older people is an international priority. Intermediate care (IC) services are regarded as an important part of the patient's pathway from the specialist to the primary care levels, bridging the gap between the hospital and the home. Patients may experience varying capacities and conditions for patient participation. Yet, few tools for evaluating patients' preferences for patient participation within IC services are at hand. Accordingly, further knowledge is needed to understand and scaffold processes for patient participation in IC. Therefore, the aim of this project was to translate, validate and pilot test the Patient Preferences for Patient Participation (the 4Ps) with patients in IC services in Norway. Methods This project comprised two phases: (1) a careful translation and cultural adaptation process, followed by a content validity trial among 15 patients and staff in Norwegian IC and (2) a cross‐sectional survey of the instrument with 60 patients admitted to IC. Results The translation between Swedish and Norwegian required no conceptual or contextual adaptations. The subsequent cross‐sectional study, designed as a dialogue between the patients and staff, revealed that only 50% of the participants received a sufficient level of patient participation based on their preferences, mostly indicating that patients were receiving less‐than‐preferred conditions for engaging in their health and healthcare issues. Conclusion The 4Ps instrument was deemed suitable for measuring patient participation based on patient preferences in the IC context and was feasible for both healthcare professionals and patients to complete in an interview when arriving at and leaving services. This may support person‐centred communication and collaboration, calling for further research on what facilitates patient participation and the implementation of person‐centred services for patients in IC. Patient or Public Contribution First, the current paper is part of the IPIC study (i.e., the implementation of patient participation in IC). Influenced by a James Lind Alliance process, the study addresses research uncertainties identified by patients, next of kin, staff and researchers in the cocreation process. Second, cognitive interviewing was conducted with 15 representatives of the target population: seven patients receiving IC services, one home‐dwelling previous IC patient (altogether four women and four men, most of them 80 years or older) and seven healthcare staff working in IC services. The interviews determined the relevance, comprehensiveness and clarity of the 4Ps. Finally, 60 patients admitted to IC took part in the cross‐sectional study.